On Typical Compact Submanifolds of the Euclidean Space - Mirzaie, R. (Український математичний журнал, 2013)
It is shown that typical compact submanifolds of Rⁿ are nowhere differentiable with integer box dimensions. Показано, що типові компактні підмноговиди простору Rⁿ ніде не диференційовні при цілих розмірностях Мінковського.